Positive Patient Response to a Structured Exercise Program Delivered in Inpatient Psychiatry - David Tomasi PhD, EdD-PhD, MA, MCS, AAT, GT; Sheri Gates MA, GT; Emily Reyns MA, R-DMT, MHC, GT (SAGE Publishing, 2019)
Background The complexity of diagnostic presentations of an inpatient psychiatry population requires an integrative approach to health and well-being. In this sense, the primary need of this research aims at developing clinical strategies and healthier coping skills for anger, anxiety, and depression; promoting self-esteem, healthier sleep, and anxiety reduction; as well as enhancing mood and emotional-behavioral regulation via exercise and nutrition education. Objectives The primary objective is to promote exercise, fitness, and physical health in inpatient psychiatry patients. The secondary objective includes therapeutic management of depressive symptoms and patient-centered approach to mania, angry outbursts, and generalized disruptive behavior. The tertiary objective is promoting research in the psychophysiological effectors of exercise and nutrition education in combination with psychotherapy. Method Monitoring self-reported changes in mood and general well-being via administration of surveys and questionnaires pre- and postexercise sessions. Results The research yielded positive outcomes in all areas investigated, suggesting the positive effects of exercise and mind-body strategies in the context of psychotherapy in inpatient psychiatry. Conclusion Physical exercise may be a helpful way to reduce mental health disorders in the context of inpatient psychiatry by targeting anxiety, depression, anger, psychomotor agitation, and muscle tension and addressing stressors and triggers and to develop a more balanced and integrated sense of self.